Dual courses of study - the supply and demand situation - Kupfer, Franziska [Verfasser]; Stertz, Andrea [Verfasser] (My University, 2011)
"For years now, Germany has witnessed steadily growing interest in dual courses of study, i. e. degree programmes that combine academic with vocational learning. A prime reason for their growing significance is that by integrating both dimensions they make it possible to equip skilled workers with fully-rounded qualifications for demanding roles in the workplace. This article describes current developments, drawing upon data from the AusbildungPlus (TrainingPlus) database." (Autorenreferat, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; G 1.3.1 Bildungsangebot & -nachfrage; Dualer Studiengang; Studienangebot; Quantitative Angaben